Neurobrucellosis - Huamán-Muñante, José (2020)
Brucellosis is a public health problem due to non-pasteurization of dairy products, with neurobrucellosis (NB) being the least common and most lethal presentation. We show the case of an 85-year-old woman who developed fever, headache and consciousness alteration. The physical examination showed motor disturbance. Serum agglutination and Bengal Rose tests were positive. Brain MRI showed ischemic lesions likely associated with vasculitis in pons, medulla oblongata and cerebellar hemispheres. The patient showed no improvement with antibiotic therapy and passed away. We emphasize the importance of suspecting NB in every febrile patient with neurological symptoms, in an endemic area like ours, for early detection and timely treatment that decreases morbidity and mortality.